2021
DOI: 10.5468/ogs.20299
|View full text |Cite
|
Sign up to set email alerts
|

Management of interstitial pregnancy in the era of laparoscopy: a meta-analysis of 855 case studies compared with traditional techniques

Abstract: Interstitial pregnancy is a rare, life-threatening condition that requires high clinical suspicion for diagnosis. Most cases are discovered after complications have occurred. Many authors have described laparoscopic management. Although previous systematic reviews have compared the attributes and complications associated with interstitial pregnancy, we endeavored to complete the first systematic review and meta-analysis to compare the laparoscopic treatment of interstitial pregnancy with the open approach in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 114 publications
2
16
0
1
Order By: Relevance
“…The selected method of surgery has variations based on the duration and outcome of the surgery as laparoscopic cornuostomy is introduced as the method of choice [ 8 ]. Although this method increases the risk of developing rupture uterus in the future pregnancy [ 10 ], laparoscopic approach is introduced to be the first line of therapy in a recent meta-analysis with the benefit of average bleeding of 168 cc that depends on the gravidity and duration of the amenorrhea that the patient has [ 11 ]. Focusing on the operative management of IP, especially the retained tissues, the benefit of hysteroscopy is recently confirmed by using morcellation techniques to avoid some complications [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selected method of surgery has variations based on the duration and outcome of the surgery as laparoscopic cornuostomy is introduced as the method of choice [ 8 ]. Although this method increases the risk of developing rupture uterus in the future pregnancy [ 10 ], laparoscopic approach is introduced to be the first line of therapy in a recent meta-analysis with the benefit of average bleeding of 168 cc that depends on the gravidity and duration of the amenorrhea that the patient has [ 11 ]. Focusing on the operative management of IP, especially the retained tissues, the benefit of hysteroscopy is recently confirmed by using morcellation techniques to avoid some complications [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three therapeutic approaches have been described: close surveillance of the ectopic pregnancy if not associated with hemodynamic instability, medical management, and surgical management. The choice hinges on various factors such as the patient's clinical status, the gestational age at the time of diagnosis, the presence of contraindications of medical treatment, and the patient's preference [21].…”
Section: Interstitial or Horn Pregnancymentioning
confidence: 99%
“…An expectant approach (surveillance) is reserved for patients with decreasing β-hCG levels and that remain clinically stable. Medical treatment with local and/ or systemic methotrexate is indicated in young nulliparous women wishing to preserve their future fertility if the interstitial pregnancy has not ruptured, if the gestational sac measures 35 mm or more in diameter, a β-hCG level of 5000 mUI/ mL or below, and the absence of embryonic cardiac activity; the rate of success is 80% [21][22][23][24].…”
Section: Interstitial or Horn Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic management of interstitial and cornual pregnancy is becoming widely accepted as a first-line management option. A recent systematic review and meta-analysis of interstitial pregnancy demonstrated laparoscopy was associated with an almost 10-fold decrease in blood loss, decreased operative time, and decreased hospital stay compared with the traditional management of laparotomy 19. Moawad et al6 reported a cumulative success rate of 85% (164/192 patients) with use of laparoscopic techniques to treat interstitial ectopic pregnancy.…”
Section: Managementmentioning
confidence: 99%